Perancangan User Experience Aplikasi Pembelajaran Digital Marketing untuk UMKM dengan Metode Human-Centered Design - Hutomo Ardianto; Ratih Kartika Dewi; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The development of technology in the last decade has grown very rapidly, especially the internet. The rapid development of the technology sector, especially the internet and the digital world, has an impact on the world of marketing. However, based on the results of McKinsey's research, only about 30% of businesses in Indonesia are developing their businesses by utilizing digital instruments. Looking at the results of this research, it can be concluded that the potential for marketing through digital instruments in Indonesia is still very large, especially for MSMEs in marketing their products online through social media Facebook and conducting online transactions, especially during the Covid-19 pandemic. However, MSME actors have difficulty to get information related to digital marketing on Facebook. This research focuses on the user experience design process on the Facebook digital marketing learning application so that the system designed meets user needs. The method used, namely Human - Centered Design (HCD) is used because at each stage of the process it involves users and can realize improvements that are more interactive and useful from the user's side. The final result of the research is a high-fidelity prototype, then the prototype is tested by usability testing. From the prototype test, the results obtained from the effectiveness aspect value of 81.42%, the overall efficiency aspect relative efficiency 100% and time-based efficiency 0.065 goals / sec, and the user satisfaction aspect using the SUS questionnaire of 86.